HUBUNGAN PARITAS DENGAN KEPATUHAN ANC TERPADU PADA TM 1 DI PUSKESMAS TEMPEH KECAMATAN TEMPEH KABUPATEN LUMAJANG - Ika Usiawati; Muthmainnah Zakiyyah; Sri Wahyuningsih (NHM PRESS, 2023)
Complications of pregnancy and delivery as the highest cause of maternal death can be prevented by prenatal checks through integrated Antenatal Care (ANC). One of the factors that influence antenatal care (ANC) visits is parity, which is the number of live births experienced by a woman. The impact of not doing ANC, especially during the first trimester, is that pregnant women will receive less information about how to properly care for pregnancy, not detecting danger signs of pregnancy early and signs of labor complications from the start. The purpose of this study is to analyze the correlation between parity and integrated ANC compliance at TM 1 at the Tempeh Health Center, Tempeh, Lumajang. The research method used is a correlational descriptive research method with a cross-sectional approach. The population in this study were 60 pregnant women who underwent antenatal care (ANC) at the Tempeh Health Center. Sampling using simple random sampling, the number of samples is 38 respondents. The research instrument used a questionnaire. The results showed that almost all primiparous respondents were obedient to ANC visits (52.6%). The results of data analysis using Spearman Rank obtained a value of 0.003 (<0.05), which means that there is a fairly strong and significant correlation between parity and integrated Antenatal Care (ANC) compliance. Pregnant women can fulfill the coverage of primary, multi, and grande-multi parity visits to get comprehensive antenatal care services and to detect complications early in their pregnancy. In addition, health workers, especially midwives, can provide counseling and education about the importance of prenatal care or ANC